1997
DOI: 10.3386/w5969
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Side of Internal Capital Markets: Divisional Rent-Seeking and Inefficient Investment

Abstract: We develop a two-tiered agency model that shows how rent-seeking behavior on the part of division managers can subvert the workings of an internal capital market. By rent-seeking, division mangers can raise their bargaining power and extract greater overall compensation from the CEO. And because the CEO is herself an agent of outside investors, this extra compensation may take the form not of cash wages, but rather of preferential capital budgeting allocations. One interesting feature of our model is that it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
600
7
14

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 489 publications
(657 citation statements)
references
References 0 publications
36
600
7
14
Order By: Relevance
“…Scharfstein (1998) argues that M & A activities destroy value because management in merging firms does a poor job allocating capital-underinvesting in divisions with relatively good investment opportunities and overinvesting in divisions with relatively poor investment opportunities. Rajan et al (2000) and Scharfstein and Stein (2000) argue that internal capital markets can hinder investment efficiency because of agency problem that may generate inefficient subsidization across business segments. Campello (2002) examines the function of internal capital markets in the investment allocation process of financial conglomerates using data from bank holding companies.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Scharfstein (1998) argues that M & A activities destroy value because management in merging firms does a poor job allocating capital-underinvesting in divisions with relatively good investment opportunities and overinvesting in divisions with relatively poor investment opportunities. Rajan et al (2000) and Scharfstein and Stein (2000) argue that internal capital markets can hinder investment efficiency because of agency problem that may generate inefficient subsidization across business segments. Campello (2002) examines the function of internal capital markets in the investment allocation process of financial conglomerates using data from bank holding companies.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Yet, empirical evidence supporting the positive performance hypotheses is surprisingly scant. While some studies have found support for the hypothesis (Chang & Choi, 1988;Keister, 1998;Khanna & Rivkin, 2001), other studies offer only mixed support and many find a negative effect and see only a dark side (Scharfstein & Stein, 2000). Indeed, much recent business group research chronicles the high costs and negative performance outcomes of group affiliation (Bertrand, Mehta, & Mullainathan, 2002;Lu & Yao, 2006;Morck, Wolfenzon, & Yeung, 2005).…”
Section: What Do Business Groups Do? the Bright And Dark Sidesmentioning
confidence: 96%
“…All business groups suffer from the adverse selection and moral hazard problems of employment in large diversified firms (e.g., Scharfstein & Stein, 2000). However, shareholders' control over managerial positions, or lack thereof, creates additional employment conflicts between professional managers and owner-appointed managers.…”
Section: Agency Costsmentioning
confidence: 98%